Comparing the Relative Reactivities of Food and Vitamin Molecules Toward Electrochemically Generated Superoxide in Dimethylformamide. Issue 5 (2nd March 2017) - Lauw, Sherman J. L.; Yeo, Joyce Y. H.; Chiang, Zhong; Webster, Richard D.
Abstract: Superoxide (O2 .− ), an anionic radical of the reactive oxygen species (ROS) family, is continuously produced in the body and can lead to the undesirable modification and damage of important biological molecules. In the present study, the relative reactivities of 18 food and vitamin molecules toward electrochemically generated O2 .− were investigated in N, N ‐dimethylformamide (DMF) solutions by using cyclic voltammetry (CV). The quenching of O2 .− was measured by monitoring the decreases in the anodic currents of the reverse peaks after the one‐electron reduction of molecular oxygen (O2 ), while systematically increasing the concentration of the test substrates. The reactivity of each compound was then approximated and compared using effective concentration indexes, EC10 and EC50, which represent the amount of compound required to reduce the concentration of the electrochemically generated O2 .− by 10 and 50%, respectively, under the present conditions. Where possible, the likely mechanisms that are involved in the scavenging of O2 .− are also discussed. Abstract : Superoxide scavenging : The voltammograms of molecular oxygen reduction are studied in the presence of increasing concentrations of various food and vitamin compounds in order to probe the relative reactivities of these molecules toward electrochemically generated superoxide.